Deep Degrowth: Contributions from Catholic Social Teaching - Baron, Chad; Mickey, Sam (The Trumpeter, 2025)
Drawing on deep ecology's critique of the obsession with growth in contemporary socio-economic systems, this article explores what the authors call deep degrowth, particularly by looking at the intersection of the degrowth movement and the religious values of Catholic Social Teaching. Following a discussion of the degrowth movement’s critique of growth, the article discusses degrowth's approach to mending colonial relations and facilitating a just distribution of resources globally. Following that, the article examines Catholic Social Teaching’s commitment to the just distribution of resources, particularly considering its concept of distributive justice. The conclusion offers some remarks about affinities between degrowth and Catholic Social Teaching as well as potential future directions for deep degrowth.